Scientific production on themes of Internal Medicine in Universidad Médica Pinareña journal - Angel Ernesto Ramos-Cordero; Eduardo Enrique Cecilia-Paredes; Katerine Otaño-Rodríguez; Guillermo Luis Herrera-Miranda; Eduardo Paz-Paula (Universidad Médica Pinareña, 2020)
Introduction: the evaluation of scientific trends in Internal Medicine affects the decision-making and training of an internist capable of providing a more comprehensive service to the sick adult population.